The Effects of Non-Pharmacological Intervention in the Management of Essential Blood Pressure - Ahlam Elkheshebi; Fadwa Alakhder; Shifaa Zarti (AlQalam Journal of Medical and Applied Sciences, 2021)
Background and Objective. Although current European and American hypertension guidelines recommend treating high blood pressure using pharmacological and no pharmacological interventions, it is unusual to use such treatment in Libyan society. This study assessed the impact of the change in lifestyle of 229 patients with essential blood pressure who are receiving medication at a follow up clinic in Central Tripoli Hospital. Methods. The study based on a questionnaire that included sociodemographic characteristics, physical activity, and medication used to regulate blood pressure during the last four months preceding the survey. Based on the blood pressure levels, patients were classified in two groups, a controlled group that did not exceed the internationally recommended level of 140/90 and another group that exceeded this level (uncontrolled group). Results The risk of hypertension was higher among elder patients (65%), men are slightly more affected by the disease (54.6%), the job stress may increase the blood pressure (71.6%), and smoking was the major cause of uncontrolled blood pressure (50.8%). On the other hand, following a patient’s diet, moderate BMI of the patient, physical activity, regardless of where and when they practiced, had a very positive effect on controlling high blood pressure. Conclusion. Patients with essential hypertension can reduce their blood pressure by changing their normal lifestyle through improving quality of nutrition and performing physical activity, in addition to continuing traditional conventional drug therapy.